Antisense Oligonucleotides for the Treatment of Dyslipidemia - Gouni-Berthold, I.; K. Berthold, H. (Current Pharmaceutical Design, 2011)
New studies further demonstrate that lowering low-density lipoprotein (LDL)-cholesterol, at least with the use of statins, decreases the risk of cardiovascular disease (CVD). Subsequently national and international guidelines have set target levels for LDLcholesterol that are progressively lower, making the likelihood of patients attaining them progressively more limited, even with the use of all currently available medications. Thus, there is a clear need for new therapeutic approaches to lower LDL-cholesterol. Antisense oligonucleotides (ASO) represent a new paradigm for the discovery of potentially powerful and selective drugs with a mechanism of action based on the concept of base-pair hybridization as described by Watson and Crick, resulting in decreased production of target proteins. In mouse and human genetic models it has been shown that decreasing hepatic apolipoprotein B-100 (ApoB-100) as well as proprotein convertase subtilisin/kexin type 9 (PCSK9) production is associated with lower circulating LDL-cholesterol levels. Purpose of this review is to discuss the available data on the effects of various ASO used for the treatment of dyslipidemia, with the main focus on ASO against ApoB-100, the most advanced in clinical development, and on PCSK9.
Keywords: apolipoproteins